Large local reactions to Hymenoptera stings: Outcome of re‐stings in real life. Issue 10 (28th May 2019) - Bilò, Maria Beatrice; Martini, Matteo; Pravettoni, Valerio; Bignardi, Donatella; Bonadonna, Patrizia; Cortellini, Gabriele; Kosinska, Magdalena; Macchia, Donatella; Mauro, Marina; Meucci, Elisa; Nittner‐Marszalska, Marita; Patella, Vincenzo; et al.
Abstract: Background: Large local reaction to Hymenoptera stings is usually defined as a swelling >10 cm which lasts longer than 24 hours, sometimes associated with erythema, pruritus and blisters. Currently, the risk of subsequent systemic reactions after re‐stings is considered low (2%‐15%). Therefore, a diagnostic workup in case of large local reaction is often judged unnecessary, as well as adrenaline auto‐injector and venom immunotherapy prescription. The aim of this study was to prospectively evaluate the outcome of re‐stings in a real‐world setting, in patients with a history of one previous large local reaction. Methods: We consecutively enrolled patients who experienced their first large local reaction (as per EAACI definition), treated with antihistamine and steroids. They were followed for field re‐stings and assessed for risk of subsequent systemic reactions. Results: We enrolled 662 patients. Out of the 225 re‐stung subjects, 24% did not experience reactions, 52% reported a second large local reaction and 24% had systemic reactions. The risk of subsequent systemic reactions was higher in case of skin test reactivity to Apis mellifera or Vespula species (OR 2.1 and 3.8, respectively), in particular if positive at 0.001 µg/mL concentration (OR 13.4 and 16.5, respectively). Conclusions: Systemic reactions, after a previous large local reaction, occur more frequently than that reported by literature. After analysing the predictive role of large local reactions for systemic reactions, we demonstrated that an accurate diagnostic workup may be considered, particularly skin tests. Further studies in different countries are needed to confirm these results and large local reaction management. Abstract : The frequency of systemic reactions, after one first large local reaction, is considerably high (24%). Skin reactivity to Apis mellifera or Vespula species seems a good risk predictor, particularly at low concentration (0.001 µg/ml). An accurate diagnostic workup should be considered for large local reactions, particularly skin testing, to assess the risk of subsequent systemic reactions and the consequent management.